NK-cell activity affected by some cytostatic drugs and their additives - Ujházy, P; Babusíková, O (Neoplasma, 1991)
The direct effect of selected cytostatic drugs on natural killer (NK) cell activity was evaluated. Peripheral blood mononuclear cells from healthy donors were tested for their cytolytic activity in vitro in the presence of adriamycin, methotrexate, leucovorin, vincristin, cytosine arabinoside and teniposide. Most of the tested cytostatic drugs did not show to be active at concentrations comparable to their plasma level. However, diluents of some preparations (cytosine arabinoside, teniposide) containing organic solutions and stabilizing additives (e.g. benzyl alcohol) suppressed the NK activity more than chemotherapeutic agents alone. Thus teniposide, containing such additives, inhibited NK activity already at 5 mg/ml, while its peak plasma concentration was 23.8 mg/ml. The inhibitory concentrations of teniposide did not affect the target binding of effector cells and the expression of 14 tested leukocyte differentiation markers. This implies that a postbinding step of the lytic process was altered by the preparation. Likewise, no inhibition of lectin dependent cellular cytotoxicity by teniposide and its diluent was observed, suggesting that the lectin may substitute the missing lytic signal.
Keywords: doxorubicin; techniky in vitro; buňky NK; Humans; Leucovorin; Antineoplastic Agents; vinkristin; Benzyl Alcohols; Fluorescent Antibody Technique; Leukemia, Erythroblastic, Acute; Methotrexate; Teniposide; protinádorové látky; methotrexát; diferenciační antigeny; Vincristine; cytarabin; akutní erytroblastická leukemie; teniposid; Cytarabine; Killer Cells, Natural; benzylalkoholy; leukovorin; Dose-Response Relationship, Drug; benzylalkohol; vztah mezi dávkou a účinkem léčiva; Benzyl Alcohol; lidé; Cytotoxicity Tests, Immunologic; Doxorubicin; cytotoxické testy imunologické; fluorescenční protilátková technika; In Vitro Techniques; Antigens, Differentiation